Fecal Short-Chain Fatty Acids Levels Were Not Associated With Autism Spectrum Disorders in Chinese Children: A Case–Control Study - Wang, Jue; Pan, Jialiang; Chen, Hengying; Li, Yan; Amakye, William Kwame; Liang, Jingjing; Ma, Bingjie; Chu, Xinwei; Mao, Limei; Zhang, Zheqing (Frontiers in Neuroscience, 2019)
Evidence from animal models supports a link between short-chain fatty acids (SCFAs), a key subset of gut microbial metabolites, and autism spectrum disorders (ASD). However, findings from human studies on this topic are unclear. We aimed to investigate whether fecal SCFAs are associated with ASD in Chinese children aged 6–9 years old. A total of 45 ASD children aged 6–9 years and 90 sex- and age-matched neurotypical controls were enrolled. High-performance liquid chromatography was applied to quantify 10 SCFA subtypes in feces. Dietary and other socio-demographic information were obtained via face-to-face interview using questionnaires. After adjustment for multiple comparisons, paired t-test analysis indicated that the fecal total and subtype SCFA concentrations were comparable in autistic children and the controls. Conditional logistic regression analysis showed that there was no significant relationship between the fecal concentration of SCFAs and the risk of ASD after adjustment for age, sex, BMI, breastfeeding, mode of delivery, parental education level, and daily energy, protein, fat, and fiber intake. In conclusion, our results did not support the hypothesis that fecal SCFA levels might be associated with the presence of ASD. However, SCFA measurement was based on a single stool sample test, so this conclusion should be treated with caution. Further studies with measurement of long-term bodily SCFA concentrations are needed to examine this relationship.